(untitled) (Medical Forum Monthly, 2022)
Objective: To analyze the pattern of CT-scan findings among head injury patients presenting to the emergency department in a tertiary care hospital. Study Design: Retrospective, observational study Place and Duration of Study: This study was conducted at the Department of Radiology / Neurosurgery, Liaquat National Hospital, June-December, 2021. Materials and Methods: Patients’ medical record files were reviewed to retries socio-demographic profiles and CT-scan findings. Data was entered in SPSS version 25 for statistical analysis. Results: 423 records were reviewed. Median age was 40 (IQR= 26 – 55) years. Majority were males (n=326, 77.1%). Top most cause of head injury was road traffic accident (n=246, 58.2%) followed by fault (n=105, 24.8%), assault (n=29, 6.9%), others (n=12, 2.8%) and unknown mechanism (n=31, 7.3%). Injury of others included all those accidental fall of objects on head. Nearly half of the patient depicted normal findings of CT scan (n=190, 44.9%). The most frequent fractured site was parietal (n=78, 18.4%), temporal (n=73, 17.3%), frontal (n=60, 14.2%), occipital (n=13, 13.1%), maxillary (n=27, 6.4%), sphenoid (n=24, 5.7%), ethmoid (n=19, 4.5%), zygomatic (n=13, 3.1%) and mandible (n=6, 1.4%). Contusions, subarachnoid hemorrhage and subdural hemorrhage was present in 36.2% (n=153), 30.3% (n=128) and 10.4% (n=44) cases respectively. Few cases presented with blood in sinuses (n=65, 15.4%), extradural hemorrhage (n=62, 14.7%), intraparenchymal hemorrhage (n=31, 7.3%), intracranial mass (n=3, 0.7%), intraventricular bleed (n=30, 7.1%). Conclusion: The current study analyzed that RTA was the leading cause of head injury and patterns of CT-scan findings was significantly different among all mechanism of injuries with a significantly higher proportion of abnormal CT-scan findings among RTA patients.